Concept of civilisation and sustainable development: a maqasidic orientation - Abdelaziz, Berghout; Saoudi, Ouahiba (Kulliyah (Faculty) of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This paper discusses the concept of “civilisation” and “civilisational sustainable development” with special reference to maqasid and values system in Islam. Islam, in its very nature, posits that civilisation is an integrated and a multi-faceted social phenomenon involving intellectual, social, socioeconomic, cultural, spiritual, moral, material, and other aspects. The concept of “civilisation” refers and links to several other social phenomena, such as development, progress, human association, umran, tamadun, maqasid, and values. Hence, studying civilisation from an Islamic perspective demands an integrated approach or rather, a civilisational framework or model. This paper addresses the following points: the concept of civilisation and civilisational development from an Islamic perspective, mapping the civilisational model for a balanced civilisation and development, maqasid framework, sustainable development goals, and reviving the civilisational vision of Islam as a precondition for civilisational development. This paper explains the leading role of the Islamic view of civilisation in the progress of society. Furthermore, it highlights the urgency of a contemporary understanding of Islam that envisions it as a project for a civilisation of creativity, balance, justice, peace, and progress. Additionally, this paper follows textual analysis and library research to discuss the main aspects that make the general framework of civilisation from an Islamic perspective; a topic of more merit and interest to the Islamic world and its development, today. The findings show the need for an integrated Islamic model of civilisation and development. The main peculiarities of civilisation in the Islamic perspective are value-loaded, balanced, comprehensiveness, maqasidic, and flexible. Additionally, it has been clearly established that, inter alia, human factors, values, maqasid, sustainable development goals, modern know-how, technological means, managerial capabilities, and governance are essential elements in the Islamic model of civilisation.